2023
DOI: 10.1038/s41598-023-37844-0
|View full text |Cite|
|
Sign up to set email alerts
|

MXene/graphene oxide nanocomposites for friction and wear reduction of rough steel surfaces

Abstract: Development of solid lubricant materials that render reliable performance in ambient conditions, are amenable to industrial size and design complexities, and work on engineered surfaces is reported. These coatings are composed of Ti3C2Tx-Graphene Oxide blends, spray-coated onto bearing steel surfaces. The tribological assessment was carried out in ambient environmental conditions and high contact pressures in a ball-on-disc experimental set-up. The evaluation yielded that the use of Ti3C2Tx-Graphene-Oxide coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Under loads of 20–50 N, the CHMC surface maintained a good sheet structure after friction (Figure c), consisting of graphene sheets. Graphene possesses several excellent characteristics, including low friction, wear resistance, and low surface energy. , The nearly vertical nanographite in the middle of CHMC promoted the continuous distribution of graphene on the surface, resulting in CHMC exhibiting good lubricity on a macroscale (Figure a). As is well-known, graphite is soft and easy to wear, but it is surprising that the nanographite in the middle of CHMC exhibited remarkably different characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Under loads of 20–50 N, the CHMC surface maintained a good sheet structure after friction (Figure c), consisting of graphene sheets. Graphene possesses several excellent characteristics, including low friction, wear resistance, and low surface energy. , The nearly vertical nanographite in the middle of CHMC promoted the continuous distribution of graphene on the surface, resulting in CHMC exhibiting good lubricity on a macroscale (Figure a). As is well-known, graphite is soft and easy to wear, but it is surprising that the nanographite in the middle of CHMC exhibited remarkably different characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Energy dissipation at tribology interface is ubiquitous in daily human life from Nano-, Micro, Meso-, Macro-, and large field of biosphere to harvest mechanical energy into electrical energy. From boundary lubrication or nanotribology to microelectromechanical systems in moving parts in presence of interfacial environment has proven to be a tribological strategy for controlling frictional drag of an engineered system [ [67] , [68] , [69] , [70] , [71] ]. The energy harvesting and reduction of environmental load can be made from transformation or researching of human motions, industrial modulation, hybrid mechanical machines, and residual mechanisms of piezo-, pyro-, thermo-, and triboelectric effect [ 72 ].…”
Section: Tribology and Electroadhesionmentioning
confidence: 99%
“…Pin-on-disk tribological tests showed that the friction coefficient and wear rate was reduced respectively by about 34.8% and 78.2% compared to base-fluid without nanoparticles. Macknojia et al [12] prepared coating containing MXene (Ti 3 C 2 T x )-graphene oxide nanocomposites on steel balls. The friction coefficient and wear rate were both lower than coatings with only Ti 3 C 2 T x or graphene oxide.…”
Section: Introductionmentioning
confidence: 99%